Analisis Faktor-Faktor Yang Mempengaruhi Minat Wakif Dalam Berwakaf Pada Cash Waqf Linked Sukuk (CWLS) Dengan Altruisme Sebagai Variabel Moderasi - Afandi, Ahmad; Harahap, Darwis; Lubis, Maisarah (Badan Wakaf Indonesia, 2022)
This study aims to see the effect of knowledge, information media, religiosity on the interest of wakif in waqf in Cash Waqf Linked Sukuk. Then the researcher added the altruism variable as a moderating variable. This type of research is descriptive quantitative research and data collection using a questionnaire technique distributed to respondents. The method of determining the sample using the Slovin formula obtained 100 research respondents. The data analysis technique used Structural Equation Modeling (SEM) with the help of SmartPLS. The research shows that the variables of knowledge, information media, religiosity and altruism have a positive effect on the interest of wakif in waqf in Cash Waqf Linked Sukuk. Then for the variable altruism cannot moderate knowledge, information media and religiosity on wakif interest in waqf in Cash Waqf Linked. The results of this study are expected to be used as a source of information and reference for those in need, especially the Indonesian Waqf Board (BWI).